#TITLE_ALTERNATIVE# - NURTAMI PRIHADI (NIM 10107061); Pembimbing : Dr. Nuning Nuraini
Virus is microscopic sized parasite which has no cellular equipment to reproduce itself. Virus is one of the disease causes and can be found in many places in our environment. Further, since the virus entered the human body, the body's immune system will react and provide resistance to the incoming antigen. In this final project discussed several models of viral dynamics. Namely, the basic model, a model anti-viral, three models of HIV: protease inhibitors, and seven models of immune response. Each model has a different type of equilibrium, there are models that only have a point of non-endemic and there are also models that have a point of non-endemic and endemic point. The occurrence of endemic condition is influenced by several parameters of the model. In this final project are also shown the numerical models of viral dynamics. In general, if the condition endemic, free virus particles will converge to a value and will still exist in the body. However, in some models, graphs of free virus particles and immune response would periodically go up and down. This is because the growth of immune cells is influenced by the reaction between virus and immune cells.